An innovation systems approach to understanding forage adoption intensity in the dairy systems of Kenya and Ethiopia - Morrison, R.; Teufel, Nils; Duncan, Alan J.; Barnes, A. (SAGE Publications, 2023)
The adoption of cultivated forages in smallholder dairy systems offers a cost-effective way to increase the productivity of livestock. The Kenyan and Ethiopian governments have both stated an ambition to increase the use of forages in their dairy sectors; however, policies have failed to produce widespread results. Existing research tends to focus on local barriers to forage adoption and not the wider innovation environment. To fill this literature gap, this study uses a Tobit model to analyse village-level data from Kenya and Ethiopia in 2015. A potentially important relationship between milk buyers and forage intensity in Ethiopia, which has not previously been addressed in the literature, is identified. As the Ethiopian government dominates the forage sector, the results of this study indicate that private milk buyers may offer an alternative source of information. In the Kenyan context, this paper finds that informal institutions and farmer-to-farmer information transmission are important in adoption decisions and should be considered when designing extension strategies.